IMPLEMENTASI GERAKAN LITERASI DI SEKOLAH (STUDI KASUS DI SDN KARAH 1 SURABAYA) - Retno Nuzilatus Shoimah (MIDA : Jurnal Pendidikan Dasar Islam, 2020)
AbstractSchool is one of the educational facilities chosen by the government as theimplementation center of the program "Surabaya Kota Literasi". Through the regulations issuedby the Surabaya city education office about the spirit of literacy in schools, it is expected that allschools in Surabaya, from elementary / equivalent level to high school / equivalent canimplement the Gerakan Literasi Sekolah (GLS) and integrate literacy capacity developmentmissions into the school curriculum.This study aims to describe the extent to which the implementation of the " GerakanLiterasi Sekolah" program at SDN Karah 1 Surabaya. Qualitative-descriptive research was usedin this study so that the literacy process in Karah 1 Elementary School can be explained clearlyand in detail. The results showed that the implementation of GLS at SDN Karah 1 was still new.Literacy support activities are still being pursued, such as: improvement of facilities and servicesin the school library, addition of book collections, procurement of reading corners in eachclassroom, enactment of compulsory reading 15 minutes before entering class, compulsoryreading at least one book in one week, and making a resume or report the contents of a book thathas been read.Some things that are still a constraint in the implementation of the literacy program atSDN Karah I are the lack of variations in reading books provided by the school and the ratio ofthe number of books to the number of students still far adrift. Supervision and encouragementfrom parents and surrounding communities is also very much needed for the success of theGerakan Literasi Sekolah.Keywords: Literacy, Gerakan Literasi Sekolah (GLS), SDN Karah 1 Surabaya